International anwendbare Streitgenossenschaftsgerichtsstände Unter besonderer Berücksichtigung der sogenannten «Menschenrechtsklagen» gegen Unternehmen - Hussmann, Lukas (sui generis Verlag, 2023)
Although the forum of the cooperative dispute has been known to some legal systems for more than two centuries, the institute is still very challenging for jurisprudence and doctrine today. This paper aims to contribute to a better understanding of the institute as well as to the fundamental question whether it is advisable to include such a place of jurisdiction in the law of international jurisdiction. Therefore, a comprehensive legal comparison between English, French, Austrian and European law is made in the first part. In the second part, there is a comprehensive analysis of the jurisdictional interests involved. In the third part, the discussion is supplemented by a practical facet, the debate on so-called "human rights claims" against corporations.